Application of the Brown Dynamics Fluctuation-Dissipation Theorem to the Study of Plasmodium berghei Transporter Protein PbAQP - Chen, Liao Y. (Frontiers in Physics, 2020)
In this article, the Brownian dynamics fluctuation-dissipation theorem (BD-FDT) is applied to the study of transport of neutral solutes across the cellular membrane of Plasmodium berghei (Pb), a disease-causing parasite. Pb infects rodents and causes symptoms in laboratory mice that are comparable to human malaria caused by Plasmodium falciparum (Pf). Due to the relative ease of its genetic engineering, P. berghei has been exploited as a model organism for the study of human malaria. P. berghei expresses one type of aquaporin (AQP), PbAQP, and, in parallel, P. falciparum expresses PfAQP. Either PbAQP or PfAQP is a multifunctional channel protein in the plasma membrane of the rodent/human malarial parasite for homeostasis of water, uptake of glycerol, and excretion of some metabolic wastes across the cell membrane. This FDT-study of the channel protein PbAQP is to elucidate how and how strongly it interacts with water, glycerol, and erythritol. It is found that erythritol, which binds deep inside the conducting pore of PbAQP/PfAQP, inhibits the channel protein’s functions of conducting water, glycerol etc. This points to the possibility that erythritol, a sugar substitute, may inhibit the malarial parasites in rodents and in humans.